Development and Evaluation of a Hygiene Learning Game for Kindergarten Children - Khun Muhammad Dalle Jasmin; Chanifah Indah Ratnasari (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
Improving clean and healthy living habits in early childhood is important because many young children still need structured support to practice daily hygiene routines consistently. This study aimed to develop and evaluate a digital learning game, Hygiene Hero: Clean Up Buddies, for kindergarten children aged four to six years. The study used a design and development approach with a prototyping model and evaluated the game through a one-group pre-test–post-test design and usability assessment using an adapted System Usability Scale. The findings showed that the game helped improve children’s hygiene knowledge and achieved high usability, indicating that the interface was appropriate and acceptable for young learners. The game was developed from classroom observations and teacher input so that the learning activities matched hygiene practices already introduced in kindergarten. This study contributes to early childhood education by showing that digital games designed around authentic classroom hygiene routines and refined through iterative feedback can serve as effective complementary media to support hygiene learning and reinforce healthy habit formation.